Aggregation induced emission transformation of liquid and solid-state N-doped graphene quantum dots. (30th April 2021) - Ozyurt, Derya; Shafqat, Sunil; Pakkanen, Tuula T.; Hocking, Rosalie K.; Mouritz, Adrian; Fox, Bronwyn
Abstract: Aggregation induced photoluminescent quenching of graphene quantum dots (GQDs) is a well-known effect, although there are limited reports of multicolour light emissions from such aggregates. In the present work, we demonstrate a novel aggregation induced bathochromic shift in emission similar to J-aggregates observed in dye molecules. Nitrogen-doped graphene quantum dots (N-GQDs) prepared in the presence of diethylenetriamine show blue emission which is attributed to monomers at low concentration (58 μg/ml) while cyan (1.75 mg/ml), and greenish yellow (3.5 mg/ml) emissions are observed at higher concentrations under 365 nm UV lamp. These materials for the first time show yellow and orange emission from drop cast film of N-GQDs under 365 nm UV-light while the parent powder gives orange emission. The variety of emission colours that could be made simply by controlling the degree of aggregation presents exciting possibilities in a range of applications such as sensing, bioimaging, solar harvesting and forensic science. Graphical abstract: Image 1